Removal of zinc(II) by activated carbon prepared from almond husks under different conditions - Hasar, H; Cuci, Y; Obek, E; Dilekoglu, MF (Multi Science Publ Co Ltd, 2003)
Activated carbon was prepared from almond husks by activation at different temperatures in the absence (MAC-I) and presence (MAC-II) of H2SO4. The ability of the activated carbon to remove zinc(II) ions by adsorption from aqueous solutions was investigated, varying several conditions such as pH, the carbonisation temperature of the husk, the initial concentration of metal ions, the contact time and the adsorbent concentration. The optimum conditions were found to be a pH value of 5.5, a carbonisation temperature of 700degreesC, a contact time of 60 min and an adsorbent concentration of 4 g/l. The results obtained indicated that effective uptake of Zn(II) ions was achieved when the carbon prepared by heating almond husks at 700degreesC was activated by the addition of H2SO4. A 92% removal of Zn(II) ions was achieved at an initial concentration of 20 mg/l and an adsorbent concentration of 4 g/l. When the adsorbent concentration was increased to 40 g/l, the adsorption density decreased from 4.5 mg/g to 0.47 mg/g for MAC-II. The Langmuir and Freundlich constants were both calculated, and the data found to be fitted reasonably well by the Langmuir isotherm. The adsorption capacities for MAC-I and MAC-II as calculated from the Langmuir isotherm were 30.864 mg/g and 35.336 mg/g, respectively.
Keywords: Aqueous-Solution; Waste-Water; Toxic Metals; Coconut Husk; Adsorption; Copper; Sorption; Cadmium; Moss; Peat